2018
DOI: 10.3233/bd-170280
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival of elderly patients with breast cancer is not related to breast-cancer specific survival: A single institution experience in Japan

Abstract: Standard multidisciplinary treatment for breast cancer prevents recurrence and metastasis and tends to extend breast cancer-specific survival even in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This was contradictory to a metaanalysis conducted by Cappellani et al 2013 that showed the same treatment outcome in elder patients as youngers ones with standard treatment, however some old women with early stage may receive less therapy [17]. In addition, another study done in Japan comparing breast cancer patients in the 70s with those in the 80s and above revealed that the standard treatment was the main factor minimizing recurrence and distant metastasis [18]. Another study done in metastatic elderly patients showed that performance status and comorbidity were the main factors leading do under treatment in patients above 75 years [19].…”
Section: Discussionmentioning
confidence: 81%
“…This was contradictory to a metaanalysis conducted by Cappellani et al 2013 that showed the same treatment outcome in elder patients as youngers ones with standard treatment, however some old women with early stage may receive less therapy [17]. In addition, another study done in Japan comparing breast cancer patients in the 70s with those in the 80s and above revealed that the standard treatment was the main factor minimizing recurrence and distant metastasis [18]. Another study done in metastatic elderly patients showed that performance status and comorbidity were the main factors leading do under treatment in patients above 75 years [19].…”
Section: Discussionmentioning
confidence: 81%
“…Deaths not connected with cancer were more common, in comparison with other causes. Standard multidisciplinary treatment for BC prevents recurrence and metastasis and tends to extend breast CSS even in older patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…16 These findings were mirrored in recent data published from Japan in which OS was significantly worse with increasing age, however breast cancer specific survival (BCSS) was not, indicating comorbidities are contributing to mortality at a greater rate than breast cancer recurrence in elderly women. 17 This is especially important to keep in mind when considering adjuvant therapies that can be associated with significant complications. Given the heterogeneity in the health status of older patients and increased rates of comorbidities, treatment decisions must be individualized in order to deliver the best possible care to this population.…”
Section: Discussionmentioning
confidence: 99%